DEVELOPMENT OF A PUBLISHING ELIGIBILITY INFORMATION SYSTEM WEB-BASED GUARANTEE INSURANCE CERTIFICATE - Magdalena, Hilyah; Santoso, Hadi; Septryanti, Ade; Destiyani, Arvina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2024)
Abstract: When working on a project that carries significant risk, the project owner asks the contractor for a letter of guarantee as a form of seriousness in carrying out the work for a certain time. One of the guarantor companies in the Bangka Belitung Islands Province is PT. Jamkrida Bangka which issues a surety bond certificate as an additional agreement to the main agreement between the project owner and the contractor. The system for submitting surety bond guarantee certificates at PT Jamkrida Bangka is still done manually starting from applying, completing the supporting document requirements, checking the suitability of the applicant's supporting documents, paying the guarantee fee, and printing the surety bond certificate as proof of guarantee. The system currently running will be developed into a web-based system to increase the speed of the administrative service process when applicants submit applications for surety bonds. The web-based system was developed using the Object-Oriented Analysis and Design method and Unified Modeling Language (UML) as a tool to develop in line with user needs. The system design can also provide easy access for applicants who are far from PT offices. Jamkrida in Pangkalpinang. Keywords: guarantee certificate; surety bonds; web-based systems; Abstrak: Pada pengerjaan proyek yang beresiko cukup besar, maka pihak pemilik proyek meminta surat jaminan kepada pihak kontraktor sebagai bentuk kesungguhan melaksanakan pekerjaannya selama waktu tertentu. Di Provinsi Kepulauan Bangka Belitung, salah satu Perusahaan penjamin adalah PT. Jamkrida Bangka yang mengeluarkan sertifikat surety bond sebagai perjanjian tambahan dari perjanjian pokok antara pemilik proyek dengan kontraktor. Sistem pengajuan sertifikat jaminan surety bond di PT Jamkrida Bangka masih dilakukan secara manual mulai dari mengajukan permohonan, melengkapi persyaratan dokumen pendukung, memeriksa kesesuaian dokumen pendukung pemohon, pembayaran biaya jaminan, dan pencetakan sertifikat surety bond sebagai bukti jaminan. Sistem yang saat ini berjalan akan dikembangkan menjadi sistem berbasis web untuk meningkatkan kecepatan proses layanan administrasi saat pemohon mengajukan permohonan jaminan surety bond. Sistem berbasis web dikembangkan dengan metode Object-Oriented Analysis and Design dan Unified Modelling Language (UML) sebagai alat bantu, agar sistem dapat berkembang selaras dengan kebutuhan pengguna. Sistem yang dirancang juga mampu memberikan kemudahan akses bagi pemohon yang secara geografis cukup jauh dari kantor PT. Jamkrida di Pangkalpinang. Kata kunci: sistem berbasis web; sertifikat penjaminan; surety bond